A primer on tRNAs, tRNA-m1A58 modification, and tRNA derivatives in T-cell activation - Zhao, Chuanxiang; Shen, Juxiang (Frontiers in Cell and Developmental Biology, 2026)
Upon antigen recognition, naive CD4+ T cells are activated, exiting quiescence to undergo rapid activation, clonal expansion, and differentiation into effector functions against pathogens. T-cell activation and clonal expansion necessitate the biosynthesis of millions of new protein copies. Recent technological advancements in small RNA sequencing have revealed a highly complex and dynamic repertoire of cellular tRNAs, tRNA-m1A58 modification, and tRNA derivatives during T-cell activation. This review outlines the basic framework of the biogenesis and biological functions of tRNAs, tRNA-m1A58 modification, and tRNA derivatives. Importantly, we elucidate how m1A58 modification regulates translation through multilevel mechanisms involving initiation, elongation, and termination. Furthermore, this review provides a comprehensive overview of the dynamic changes in tRNA expression repertoires and the impacts of tRNA-m1A58 modification and tRNA derivatives on T-cell activation. This review aims to offer novel insights into the molecular mechanisms underlying T-cell activation, facilitating the development of more effective therapeutic strategies for treating T-cell-related diseases.